Assessment of Carbon Dioxide Captured in Producer Biomass and Its Influencing Factors in a Tropical Freshwater Reservoir - Phrommarat, Bhanupong; Buawech, Dirakrit (Journal of Food Health and Bioenvironmental Science, 2023)
Since the impact of global warming and climate change due to emissions of greenhouse gas is increasingly serious, freshwater aquatic ecosystems are considered to be one of the most important natural carbon sinks. The key process of the carbon cycle and energy flow in the system is photosynthesis where CO2 is fixed to produce organic compounds by aquatic producers or phytoplankton. The concept of net primary productivity (NPP) is generally used to describe the net amount of energy and CO 2 stored in producer biomass. Nonetheless, phytoplankton primary production depends directly on various physicochemical as well as biological factors. This study investigated the variation of NPP to estimate CO2 absorption in relation to the influence of physicochemical parameters in tropical freshwater ecosystems by using Srakaew reservoir as a case study. Water samples were collected in three consecutive seasons during September 2018 to April 2019. The results revealed that CO 2 captured by phytoplankton in the reservoir to produce their biomass or NPP range from 350 to 5,777 mg m-2 day-1 (mean = 2,813 mg m-2 day-1). CO2 absorption displayed a significant linear relationship with light intensity and water temperature. Seasonal variation can affect NPP and CO2 absorption. In the hot season, NPP and CO2 absorption in the water were significantly higher than the cool season while there was no significant difference in the rainy season compared with the other seasons. According to the trophic state assessment, Srakaew reservoir was classified as eutrophic and hypereutrophic due to its low Secchi transparency coupled with high nutrient levels in the water.